«El irracional es el otro»: Los mecanismos de la interpretación en Antropología - Ricard Lanata, Xavier (Pontificia Universidad Católica del Perú. Fondo Editorial, 2005)
This article examines two dialogues between the anthropologist and alpaca shepherds of the Ausangate mountains (Cusco region, province of Canchis). Parting from the description and analysis of the concrete interpretation mechanisms used in the anthropological discipline (establishment of a lexicon, logical inferences, etc.), and of its consequences (in particular, the attribution of a pre-rational or irrational mentality, on behalf of the anthropologist, to his farmer-indigent interpreters), the article proposes reflection on the methodological obstacles for an adequate anthropological interpretation of the other cultures. It attempts in this way, to contribute to define, from the hermeneutic practice of anthropology, methodological protection that guarantee the constitution of real spaces of intercultural dialogue.

Este artículo examina dos diálogos entre el antropólogo y pastores de alpacas de la cordillera del Ausangate (región Cusco, provincia de Canchis). A partir de la descripción y del análisis de los mecanismos concretos de interpretación utilizados en la disciplina antropológica (establecimiento de un léxico, inferencias lógicas, etc.), y de sus consecuencias (en particular, la atribución de una mentalidad prerracional o irracional, por parte del antropólogo, a sus interlocutores campesino-indígenas), el artículo propone una reflexión sobre los obstáculos metodológicos para una adecuada interpretación antropológica de las culturas otras. De esta manera pretende contribuir a la definición, desde la práctica hermenéutica de la Antropología, de resguardos metodológicos que garanticen la constitución de reales espacios de diálogo intercultural.
«The irrational is the other»: The mechanisms of interpretation in Anthropology
Keywords: Análisis hermenéutico; Diálogo intercultural; Cultura andina; https://purl.org/pe-repo/ocde/ford#5.04.03